Promising practices for family and community involvement during high school - Shumow, Lee (Family, school, community, partnership issues., 2009)
This volume focuses on family and community connections with education during the high school years. In comparison to the wealth of attention that has been focused on involving parents with schools during the early childhood and elementary school years, less attention has been directed to parents of high school students and fewer educational programs have been developed to forge connections between family, community, students, and educators at the high school level. Researchers have found that family and community have a very significant impact on student achievement and on post secondary attainment despite the considerable decline in parental involvement by high school. Educators know that family and community factors are important for student success in high school while, at the same time, they identify working with families and connecting the curriculum to the community as difficult.Currently, scholars from various fields are involved in conducting research to better understand how schools can best enhance the education of the young through interactions with students' families and communities. Educational practitioners also are pioneering efforts to involve and serve families as well as to connect with communities in order to enrich the educational environment and enlarge opportunities for students, teachers, families, and community members. This volume, which will be of interest to both researchers and educators, reflects the interdisciplinary nature of the field. The contributors were recruited from diverse fields and workplaces.Chapters are organized into two sections to reflect whether the genesis of the work described is from theory and research or from practice and policy. Chapters originating from theory and research address: adolescent development and family involvement; the role of family and community in extracurricular activity participation; and the evolution of trust relationships in school community partnership development. Chapters originating from practice and policy address: transition to high school, using the community as a "text" for learning; career education partnerships with businesses, post secondary institutions, and community organizations; as well as, state policies and programs that support parental involvement in postsecondary planning.